Campaigner for migrants in Libya targeted in spyware attack - Giuffrida, Angela; Kirchgaessner, Stephanie (The Guardian, 2025)
An Italy-based human rights activist whose work supports the international criminal court in providing evidence about cases of abuse suffered by migrants and refugees held in Libyan detention camps and prisons has revealed that Apple informed him his phone was targeted in a spyware attack.
Keywords: Africa; Europe; Giorgia Meloni; Hacking; International criminal court; Italy; Libya; Middle East and north Africa; Migration; Technology; WhatsApp; World news